Evaluation of gal-3 Gene Expression and its related to some Immunological Markers in patients with Beta Thalassemia Major (International Journal of Environmental Sciences, 2025)
One of the most prevalent hereditary autosomal single-gene illnesses in the world, beta-thalassemia major is also present in the Iraqi population. In order to perform this study, 75 blood samples were taken from pediatric hospital patients with β-thalassemia major in Wasit Province, and 25 people who appeared to be in good condition served as controls. The study period was extended from November 2023 to February 2024.The findings displayed the gender-specific distribution of β-thalassemic major (βTM) patients, with no discernible differences between the 38 males (51.35%) and the 36 females (48.65%). The age distribution of the βTM patients showed that the largest group of patients were between the ages of 10 and 20, represented by 38 (51.35%), followed by those between the ages of 21 and 30, represented by 15 (20.27).The When compared to the healthy control group, which had a record of 172.45 ±37.27 ng/ml and 24.55 ±6.35 pg/ml, respectively, the ELISA assay revealed a significant rise in IL-35 and IL-37 (371.64 ±21.01 pg/ml) and 69.56 ±5.76 pg/ml). The gal-3 gene expression was assessed by quantitative real-time PCR, which revealed a substantial (P≤0.05) drop in patient expression (0.374±0.18) as compared to the control, which recorded 1.00 ±0.00 fold.